Making a case for national policy direction on the protection of built heritage : examining approaches to heritage protection in district plans produced by territorial authorities in the Otago region under the Resource Management Act 1991 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resource and Environmental Planning at Massey University, New Zealand - Travis, Lucy Charlotte (Massey University, 2024)
Heritage conservation has many justifications. Most notably, built heritage has sociocultural value as a tangible symbol of our history and culture. As a result, the conservation of built heritage has long been recognised as important, although its protection in planning is a relatively recent phenomenon. In this context, the theoretical foundations of heritage conservation have rapidly evolved over time, creating multiple different conceptualisations of how heritage should be protected. In Aotearoa New Zealand, district plans produced by territorial authorities under the Resource Management Act 1991 play a key role in the protection of built heritage. Focusing on the Otago region, this research examines how territorial authorities implement heritage conservation in district plans to protect built heritage. It explores the international evolution of heritage conservation and its application in planning, identifying what heritage protection should look and highlighting tensions between the competing discourses that shape its implementation within planning. Through a case study approach, this research identifies and compares protection methods implemented in the district plans of five territorial authorities in the Otago region. This examination reveals varied approaches to the protection of built heritage in the Otago region and identifies an opportunity to align local practice with international developments. This research asserts that stronger policy guidance is needed, focusing on the potential of a National Policy Statement to provide a more cohesive direction for heritage protection.
Fair dealing exclusions under the Copyright Act 1994 may apply to the reproduction of Tables and Figures.
Keywords: 330103 Architectural heritage and conservation; 430205 Heritage and cultural conservation